Impaired GABA Neural Circuits Are Critical for Fragile X Syndrome - Fei Gao; Lijun Qi; Zhongzhen Yang; Tao Yang; Yan Zhang; Hui Xu; Huan Zhao (Neural Plasticity)
Fragile X syndrome (FXS) is an inheritable neuropsychological disease caused by silence of the fmr1 gene and the deficiency of Fragile X mental retardation protein (FMRP). Patients present neuronal alterations that lead to severe intellectual disability and altered sleep rhythms. However, the neural circuit mechanisms underlying FXS remain unclear. Previous studies have suggested that metabolic glutamate and gamma-aminobutyric acid (GABA) receptors/circuits are two counter-balanced factors involved in FXS pathophysiology. More and more studies demonstrated that attenuated GABAergic circuits in the absence of FMRP are critical for abnormal progression of FXS. Here, we reviewed the changes of GABA neural circuits that were attributed to intellectual-deficient FXS, from several aspects including deregulated GABA metabolism, decreased expressions of GABA receptor subunits, and impaired GABAergic neural circuits. Furthermore, the activities of GABA neural circuits are modulated by circadian rhythm of FMRP metabolism and reviewed the abnormal condition of FXS mice or patients.